Popcultured : thinking Christianly about style, media and entertainment - Turner, Steve, 1949- (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2013)
There's no avoiding popular culture -- we've been enculturated into it. What does it mean to be faithful Christians in a pop culture world? How do we think Christianly about celebrity and leisure? Some Christians try to abstain from "worldly" pursuits, while others consume culture indiscriminately, assuming it has little effect on them. But if Christ is Lord of all of life, then there ought to be Christian ways to engage with and appreciate popular culture. Steve Turner has spent his career chronicling and interviewing people from the worlds of music, film, television, fashion, art and literature. Now he provides an insider's guide to a wide range of entertainment pursuits, with biblical frameworks for understanding pop culture genres and artifacts. Turner explores: how movies use redemptive narratives and parables; ways journalistic headlines convey worldview assumptions; differences between famous people in the past and celebrities today; what ideas are communicated through clothing and fashion design; how technology changes our sense of what is real; and much more. God entrusts culture to us and gives us the ability to critique it, enjoy it and create it. This book will help you become a better cultural critic, consumer and creator. - Publisher.
Introduction: we've been popcultured -- Leisure pursuits : why we should care -- Popular culture : defining the term -- Working it out : some biblical parameters -- Cinematic art : the story of stories -- Journalism : reading between the lines -- Celebrity culture : the game of the fame -- Fashion : the language of clothes -- Ever-greater thrills : the search for sensation -- Comedy : laughs lies and truth -- Advertising : the hidden persuader -- Technology : rewiring our world -- Photography : the opening of the eyes -- TV and movies : the image of the faith -- What should I do : consuming, critiquing, creating.
Includes bibliographical references (pages 235-246) and index.
Keywords: Popular culture -- Religious aspects -- Christianity